Modelling the impact of laser micro-joint shape and size on resistance and temperature for Electric Vehicle battery joining application. (15th August 2022) - Das, Abhishek; Masters, Iain; Haney, Paul
Abstract: Laser micro-welding is increasingly being used to produce electrically conductive joints for automotive battery packs or energy storage devices to weld tabs to cylindrical cell terminals or pouch cell tabs to a busbar. There is little research currently existing in the literature reporting the joint characteristics in terms of electrical resistance and temperature rise due to charge-discharge current. This paper focuses on characterising and modelling electrical and thermal behaviours of laser micro-welds considering different shapes and sizes of the welding seam. A wide variety of laser joint shapes, including linear seam, multiple laser spots, circular seam, cross-seam and square seam were investigated with varying seam sizes considering 0.3 mm copper and Hilumin steel tab materials. Results showed that under-weld, good-weld and over-weld had a high impact on mechanical strength and fusion zone characteristics, however, the electrical resistance and temperature rise behaviours were not influenced by these weld categories. The linearized resistivity model was able to capture the effect of Joule heating and predicted resistance and temperature behaviours within ±6% error. The suitability of multiphysics electrical and thermal modelling for predicting the resistance and temperature behaviours at the early design stage has been demonstrated. Graphical abstract: Unlabelled Image Highlights: Multi-physics simulation models to predict joint's resistance and temperature rise for safe operation in EV battery pack. Effect of various weld shapes and sizes (i.e. laser spots, linear-, circular-, cross- and square seams) were investigated. The developed model can predict the joint resistance and temperature within ± 6% of the experimentally obtained results. The current density analysis showed that a circular seam was better to avoid current concentration at the joint location.